If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6w + 5 = w + -35 Reorder the terms: 5 + 6w = w + -35 Reorder the terms: 5 + 6w = -35 + w Solving 5 + 6w = -35 + w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-1w' to each side of the equation. 5 + 6w + -1w = -35 + w + -1w Combine like terms: 6w + -1w = 5w 5 + 5w = -35 + w + -1w Combine like terms: w + -1w = 0 5 + 5w = -35 + 0 5 + 5w = -35 Add '-5' to each side of the equation. 5 + -5 + 5w = -35 + -5 Combine like terms: 5 + -5 = 0 0 + 5w = -35 + -5 5w = -35 + -5 Combine like terms: -35 + -5 = -40 5w = -40 Divide each side by '5'. w = -8 Simplifying w = -8
| 3(2t^2-5)=t | | -5x+-5=9x | | a^2x^2-8abx+16b^2=0 | | 97-4x=41x+17 | | 9=a(14) | | 11-10x=40-17x | | 10x+35=28x+35 | | -74-9x=7x+22 | | 8p-24+10p=138 | | 19r=304 | | 2x+10=-20-8x | | 9a=14 | | 3x-4-x=2x-4 | | r-17=20 | | 124-6x=2x+20 | | 2x+(4x+1)=15 | | 3x-8=0 | | 28+2n=14 | | -9x+15=-22-4(x+22) | | 2x+7(.5)=2 | | 10+8x=4x+16 | | 12h=156 | | -3-6x=6-7x | | 4h(2+6h)= | | 8x^2+33x-35= | | 10=2x-3 | | 12=156h | | -4x-32=-72 | | 3g-2(g+4)=8(g-1) | | 7m=-35 | | 4(1+-3.5y)+2y=-2 | | -2f+6=10 |